3D surface reconstruction scheme for dynamic objects: Principle and implementation. (30th September 2022) - Wang, Jianhua; Yang, Yanxi
Highlights: A new dual-step phase shift method is proposed for wrapped phase calculation in dynamic 3-D measurement. Dual-frequency dual-step phase shift method is further proposed for unwrapped phase calculation. The influence of ambient light on the proposed dual-frequency dual-step phase shift method is analyzed. Abstract: This paper introduces a high-speed, low-cost and easy-to-implement three dimensional (3D) surface measurement approach for dynamic objects. First, we proposed a new dual-frequency dual-step phase shift method to extract unwrapped phase, which has high accuracy and few fringes. We also analyzed the influence of ambient light on the proposed method. Secondly, we compare a variety of dither binarization methods and chose a suitable error diffusion kernel. Finally, we introduce the implementation of the dynamic 3D measurement system. Experiments on 3D measurement of dynamic objects demonstrate the valid of the proposed scheme. Further comparison of the phase accuracy between the proposed method and existing methods confirms the robustness of the proposed dual-frequency dual-step phase shift method.